Heavy Metal Contain in Drinking Water Collected From Nampala Gold Mine Wells - Dackouo, Blaise; Toure, Hamadoun Abba; Mariko, Madani; Coulibaly, Bernadette; Naco, Mohamed El Béchir; Kanoute, Gaoussou; Koumare, Benoît Yaranga; Bouatia, Mustapha (European Journal of Applied Sciences, 2024)
Heavy metal pollution is global health threat. The aim of this study was to assess some phyco-chemical parameters in Nampala well waters. High concentrations of Nickel and Iron linked to the mineral ore contain of the area were detected instead of a pollution issue.